3D interconnected porous biomimetic scaffolds: In vitro cell response. Issue 12 (30th April 2013) - Panzavolta, Silvia; Torricelli, Paola; Amadori, Sofia; Parrilli, Annapaola; Rubini, Katia; della Bella, Elena; Fini, Milena; Bigi, Adriana
<x xml:space="preserve">Abstract</x> Bone cell response to 3D bioinspired scaffolds was tested on osteoblast culture supernatants and by means of quantitative polymerase chain reaction (qPCR). Foaming and freeze‐drying method was optimized in order to obtain three‐dimensional interconnected porous scaffolds of gelatin at different contents of nanocrystalline hydroxyapatite (HA). Addition of a non toxic crosslinking agent during foaming stabilized the scaffolds, as confirmed by the slow and relatively low gelatin release in phosphate buffer up to 28 days. Micro‐computed tomography reconstructed images showed porous interconnected structures, with interconnected pores displaying average diameter ranging from about 158 to about 71 μm as the inorganic phase content increases from 0 to 50 wt %. The high values of connectivity (>99%), porosity (> 60%), and percentage of pores with a size in the range 100–300 μm (>50%) were maintained up to 30 wt % HA, whereas higher content provoked a reduction of these parameters, as well as of the average pore size, and a significant increase of the compressive modulus and collapse strength up to 8 ± 1 and 0.9 ± 0.2 MPa, respectively. Osteoblast cultured on the scaffolds showed good adhesion, proliferation and differentiation. The presence of HA promoted ALP activity, TGF‐β1, and osteocalcin production, in agreement with the observed upregulation of ALP, OC, Runx2, and TGF‐β1 gene in qPCR analysis, indicating that the composite scaffolds enhanced osteoblast activation and extra‐cellular matrix mineralization processes. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 3560–3570, 2013.